Effect of brassin-like substance on the quality of early germinated arabica coffee bean (Coffea arabica L.) - Primluck Praphutphitthaya (2018)
Arabica coffee beans were monitored to evaluate the changes of chemical compositions during early germination period after soaking with brassin-like substance (BS). The experiment was designed as 4×5 factorial in completely randomized design (CRD) by soaking coffee seeds into BS at 4 different concentrations (0 (control), 0.5, 1.0 and 2.0 mg/L), which considered as factor 1. Chemical compositions were determined at 5 germination times (before soaking, day 2, 4, 6 and 8 after soaking), which considered as factor 2. Three replications were made on each combination and each replication consisted of 100 coffee seeds. The results showed that chemical compositions and antioxidant activity were clearly effected by BS and germination time. Caffeine content significantly declined upon BS concentrations. Furthermore, the content also gradually decreased during early germination. Interestingly, soaking coffee seeds in 2.0 mg/L BS could enhanced the greatest amount of chlorogenic acid content within 4 days after soaking. The compound, however, sharply declined afterward. BS could decrease total phenolic compounds in germinated coffee seeds. BS applications at concentrations of 1.0 and 2.0 mg/L also showed greater antioxidant activity than those seeds applied by BS 0.5 mg/L and the control. Moreover, radical scavenging activity of coffee seed crude extracts also indicated that the activity tended to increase during early germination.